2017
DOI: 10.1021/acsami.7b02241
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Mg2+–Ca2+ Switch on the Development of Bone Mimetic Hydroxyapatite

Abstract: Ionic substitution can affect essential physicochemical properties leading to a specific biological behavior upon implantation. Therefore, it has been proposed as a tool to increase the biological efficiency of calcium phosphate based materials. In the following study, we have evaluated the contribution of an important cation in nature, Mg, into the structure of previously studied biocompatible and biodegradable hydroxyapatite (HA) nanorods and its subsequent effect on its chemical, morphology, and bone mimeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 56 publications
4
45
0
Order By: Relevance
“…The raw samples exhibited broad peaks, and after calcination, their width decreases. Figure shows that raw samples are constituted by ordered crystals; consequently, their peak widths are the result of elastic and inelastic diffraction contributions and are not due to a low crystalline quality (order) as have been previously pointed out . It is clear that if the raw crystals are nanometric and ordered, these have to influence the vibrational states of the IR and Raman spectra.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…The raw samples exhibited broad peaks, and after calcination, their width decreases. Figure shows that raw samples are constituted by ordered crystals; consequently, their peak widths are the result of elastic and inelastic diffraction contributions and are not due to a low crystalline quality (order) as have been previously pointed out . It is clear that if the raw crystals are nanometric and ordered, these have to influence the vibrational states of the IR and Raman spectra.…”
Section: Resultssupporting
confidence: 55%
“…Figure 1 shows that raw samples are constituted by ordered crystals; consequently, their peak widths are the result of elastic and inelastic diffraction contributions and are not due to a low crystalline quality (order) as have been previously pointed out. [18,25,26] It is clear that if the raw crystals are nanometric and ordered, these have to influence the vibrational states of the IR and Raman spectra. Figure 4a-d shows the IR bands located between 400 to 4,000 cm −1 for raw and calcinated samples and Sigma-Aldrich.…”
Section: Sem Analysismentioning
confidence: 99%
“…A reduction of both the crystallite size and degree of crystallinity after Ca substitution by Mg was also reported. 42 Consequently, almost the same reduction in the crystallinity degree of pure HAP was observed for all multisubstituted HAPs, rather independent of the increasing amount of Sr in HAPc lattice. Therefore, it clearly appears that the Sr amount has a minor impact on the crystallinity of triple-substituted HAPc, in this range of concentration.…”
Section: -supporting
confidence: 52%
“…17 The effect of Mg, as a substituting element in HAP-Mg, on HAP characteristics is a subject of numerous different studies. 16,17,[37][38][39][40][41][42][43] Clearly, Mg is involved in skeletal metabolism and bone growth by increasing osteoblast cell activity and avoiding osteopenia and bone fragility, and thus playing an essential role in bone remodeling. 16,17,37 It was also suggested that Mg deficiency is linked to osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…Although the potential difference of corrosion micro-galvanic α-Mg/Mg 17 Sr 2 is less than that of α-Mg/Ca 2 Mg 6 Zn 3 , α-Mg is etched as an anode in two pairs of micro-galvanic, so the role of α-Mg/Mg 17 Sr 2 and α-Mg/Ca 2 Mg 6 Zn 3 in the corrosion process is similar. The α-Mg corrosion near the second phase was faster, resulting in an increase in the concentration of Mg and Ca ions nearby and the formation of bulk HA with a smaller volume [26]. Part of the HA is formed by wrapping H 2 and becomes a chimney-like structure.…”
Section: Discussionmentioning
confidence: 99%